2017
DOI: 10.1016/j.meegid.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparison of RCMV ALL 03 open reading frame (ORF) among several different strains of cytomegalovirus worldwide

Abstract: Genomic analysis of RCMV ALL-03 provided an overall picture of the whole genome organization and it served as a good platform for further understanding on the divergence in the family of Herpesviridae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Next, to elucidate the genomic features of ORFV strain UPM/HSN-20, a high-throughput DNA-sequencing approach was employed, a technique that proved to be efficient in revealing detailed genetic information of an organism. In addition to identifying pathogens faster, NGS technology and bioinformatics can provide new insights into the molecular mechanism of microbial pathogenesis ( Balakrishnan et al, 2017 ; Gwinn et al, 2019 ). Compared to Sanger sequencing, NGS technology has enabled researchers to study and understand the microbial world from broader and deeper perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to elucidate the genomic features of ORFV strain UPM/HSN-20, a high-throughput DNA-sequencing approach was employed, a technique that proved to be efficient in revealing detailed genetic information of an organism. In addition to identifying pathogens faster, NGS technology and bioinformatics can provide new insights into the molecular mechanism of microbial pathogenesis ( Balakrishnan et al, 2017 ; Gwinn et al, 2019 ). Compared to Sanger sequencing, NGS technology has enabled researchers to study and understand the microbial world from broader and deeper perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the development of many animal models for the virus. 41 46 Seroprevalence studies have shown that 30–97% of the population is seropositive for CMV. 47 – 49 The immune system can easily control the virus from causing active infection and facilitating lifelong latency.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Interestingly, this local strain (RCMV ALL-03) has been identified crossing the placenta infecting the pups making it suitable for congenital infection animal model (33). The availability of the complete genome sequence of this virus add on more advantages for pathogenicity study and antiviral development (34,35). Therefore, this study was conducted to screen combinations of siRNA for their cytotoxicity level and their effectiveness on inhibiting RCMV ALL-03 virus replication and gene expression.…”
Section: Introductionmentioning
confidence: 99%